2021
DOI: 10.1177/1535370221997363
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenesis and brain functional imaging in nocturnal enuresis: A review

Abstract: Nocturnal enuresis is a common and distressing developmental disease, which may cause various degrees of psychosocial stress and impairment to self-esteem in affected children as well as agitation to their parents or caregivers. Nevertheless, the etiology and pathogenesis of nocturnal enuresis are not understood. Currently, nocturnal enuresis is generally considered a multifactorial disease associated with a complex interaction of somatic, psychosocial, and environmental factors. A variety of postulations have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 68 publications
1
10
0
Order By: Relevance
“…In addition, these potential causes of morbidity, such as bladder, vasopressin, and sleep, are also shown on the top 20 keyword lists. These factors have been widely reported (6,47). At present, there are two theories about bladder function derangements.…”
Section: Pathogenesismentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, these potential causes of morbidity, such as bladder, vasopressin, and sleep, are also shown on the top 20 keyword lists. These factors have been widely reported (6,47). At present, there are two theories about bladder function derangements.…”
Section: Pathogenesismentioning
confidence: 99%
“…Epidemiological studies have shown that the prevalence of NE varies across regions, but the global overall prevalence ranges from 4 to 16% (3,4). Nearly 15% of children with mild symptoms recover on their own each year without any intervention (5), but 1-2% of children with severe conditions will continue to experience symptoms into adulthood (6). Moreover, severe NE can lead to troublesome problems such as psychosocial issues, low self-esteem, fear of sleepovers, and social isolation (7,8); it is also difficult for the families affected.…”
Section: Introductionmentioning
confidence: 99%
“…(2) slice-timing to correct the remaining time points; (3) realignment; (4) normalizing to Montreal Neurological Institute (MNI) template as well as resampling into a new 3 × 3 × 3 mm 3 voxel size by using T1 image unified segmentation; (5) smoothing with a Gaussian kernel (full-width-half-maximum, FWHM of 6 mm); (6) detrending; (7) regressing common covariates out, including Friston's 24 head motion parameters (32), white matter (WM), and cerebrospinal fluid (CSF) signals; (8) filtering (0.01-0.08 Hz). There were 3 children with PNE and 4 HCs excluded for excessive head motion (translation > 2 mm, rotation > 2 • ).…”
Section: Data Preprocessingmentioning
confidence: 99%
“…It is generally believed that nocturnal polyuria, arousal dysfunction, and abnormal nocturnal bladder function are three main factors implicated in the pathogenesis of PNE (4)(5)(6), and maturational delays of the central nervous system have been considered to be related to the pathogenesis of PNE (7). Over the past few decades, magnetic resonance imaging (MRI) technology, especially functional MRI (fMRI), has been validated as an efficient, non-invasive, and promising approach to investigating the neural mechanisms of bladder control in healthy and pathological participants (8).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation